Factors Influencing Investment Decision Making in Foreign Exchange: Financial Literacy, Risk Perception, Loss Aversion - Rindu Reza Budiarti; Sri Trisnaningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Public interest in forex investment is increasing along with easier access to information and technological developments. However, many forex traders make investment decisions without adequate knowledge and consideration of risk. This study aims to examine the influence of financial literacy, risk perception, and loss aversion on forex investment decisions. The research population consists of forex traders in Surabaya with specific criteria. Questionnaires were distributed online using Google Forms as a data collection instrument. The research employs a quantitative approach using primary data and Partial Least Square (PLS) analysis. The results indicate that high levels of financial literacy enhance traders' ability to gather and analyze information before investing. Good risk perception encourages traders to be more cautious in facing forex market fluctuations. Loss aversion influences traders to avoid significant losses, leading them to be more selective in choosing investment strategies. These psychological factors become increasingly relevant with technological advancements and the ease of accessing trading platforms.